Challenges and Benefits of ‘Work from Home’ for employees in the Kingdom of Bahrain - Moovala, Vijayalaxmi (Advances in Social Sciences Research Journal, 2020)
COVID-19 ushered in a range of strategic, structural, and operational changes in organisations. Significant among these changes being the work from home (WFH) arrangement. The main aim of this study was to identify the challenges and benefits that the WFH arrangement brought in its wake, for employees in the Kingdom of Bahrain. The similarities and differences in the challenges faced, and benefits reaped by different demographic segments of respondents, namely; male and female, managers and non-managers, and the four generations [Baby-boomers, Gen X, Millennials, and Gen Z] were examined. The study revealed that the major challenges faced by respondents of these segments were receiving work requests from managers and colleagues after scheduled work hours and/or at their convenience, keeping a regular schedule, keeping family members away from workspace- especially during virtual meetings, not having access to the tools or information needed for the job, not having workspace/workstation at home, and communication with colleagues being hard. The major benefits listed were saving commute time, flexible working, work life balance, personal and family care, and more focus. The general preference of majority of the respondents was to continue with WFH arrangement - half the time in the future. The findings of this study threw light on the need for organisations to formulate policies for overcoming the challenges faced by respondents during WFH. This would result in better productivity and contribute to the employees’ well-being.